2012
DOI: 10.1007/s00402-012-1578-4
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of in vivo bioactivity and compressive strength of a novel superporous hydroxyapatite with beta-tricalcium phosphates

Abstract: These findings should be kept in mind when choosing the highly porous ceramics.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 30 publications
0
12
0
2
Order By: Relevance
“…Okanoue et al . reported that resorption of β-TCP granules was not necessarily accompanied by bone ingrowth in a rabbit bone defect model [13]. Generally, rodents have higher bone metabolic activity than other mammals, which can induce rapid granule degradation and new bone formation [17].…”
Section: Discussionmentioning
confidence: 99%
“…Okanoue et al . reported that resorption of β-TCP granules was not necessarily accompanied by bone ingrowth in a rabbit bone defect model [13]. Generally, rodents have higher bone metabolic activity than other mammals, which can induce rapid granule degradation and new bone formation [17].…”
Section: Discussionmentioning
confidence: 99%
“…Briefly, when compared to both α- and β-TCP, HA is a more stable phase under the physiological conditions, as it has a lower solubility (Table 1) and, thus, a slower resorption kinetics [137,138,139,140]. Therefore, the BCP concept is determined by the optimum balance of a more stable phase of HA and a more soluble TCP.…”
Section: Bioceramics Of Calcium Orthophosphatesmentioning
confidence: 99%
“…Thus, porous calcium orthophosphate implants cannot be loaded and are used to fill only small bone defects. However, their strength increases gradually when bones ingrow into the porous network of calcium orthophosphate implants [139,585,586,587,588]. For example, Martin et al reported bending strengths of 40–60 MPa for a porous HA implant filled with 50%–60% of cortical bone [585], while in another study an ingrown bone increased strength of porous HA bioceramics by a factor of 3 to 4 [587].…”
Section: The Major Propertiesmentioning
confidence: 99%
“…Hydroxyapatite (HAP), the chemically pure version of the mineral component of bone, however, is typified by impractically low resorption rates [13]. Reduction of the particle size [4], an increase in porosity [5] and introduction of ionic substitutions, such as magnesium [6], sodium [7], fluorine [8] and/or carbonate [9], so as to mimic the composition and microstructure of biological apatite, have presented approaches to resolving this issue, though with limited success. Namely, even the least sparingly soluble calcium-deficient apatites usually resorb slower than the new bone tissue formation rate [10], whereas HAP with high porosity is weak even to compression and not suitable for load-bearing applications [11].…”
Section: Introductionmentioning
confidence: 99%